Prodrug Strategies in Ocular Drug Delivery - Barot, Megha; Bagui, Mahuya; R. Gokulgandhi, Mitan; K. Mitra, Ashim (Medicinal Chemistry, 2012)
Poor bioavailability of topically instilled drug is the major concern in the field of ocular drug delivery. Efflux transporters, static and dynamic ocular barriers often possess rate limiting factors for ocular drug therapy. Different formulation strategies like suspension, ointment, gels, nanoparticles, implants, dendrimers and liposomes have been employed in order to improve drug permeation and retention by evading rate limiting factors at the site of absorption. Chemical modification such as prodrug targeting various nutrient transporters (amino acids, peptide and vitamin) has evolved a great deal of interest to improve ocular drug delivery. In this review, we have discussed various prodrug strategies which have been widely applied for enhancing therapeutic efficacy of ophthalmic drugs. The purpose of this review is to provide an update on the utilization of prodrug concept in ocular drug delivery. In addition, this review will highlight ongoing academic and industrial research and development in terms of ocular prodrug design and delivery.
Keywords: suspension